Taber Laut Local Wisdom as A Social Regulation and Safety Valve for Natural Resource Conflicts in Batu Beriga Village - Putra, Vebriansyah Pratama; Syafitri, Anggie Tri; Charlie, Charlie; Rani, Milia; Rahmadani, Subri; Sulaiman, Aimie (Universitas Tanjungpura, 2025)
Taber Laut is a form of local wisdom of the Batu Beriga Village community which is interpreted as an expression of gratitude for the abundant marine products and as a tribute to ancestors. This study aims to analyze other functions of Taber Laut in Batu Beriga Village, namely as a social regulation and a safety valve for conflicts over the use of natural resources. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth reporting, focus group discussions, documentation, and literature studies. The results show that Taber Laut is not only understood as an annual ritual, but also contains customary mechanisms that function to regulate community behavior, create social order, and serve as a tool of social control. The customary rules born from this tradition are conveyed by the traditional leader and mutually agreed upon, so that they have normative power in regulating the activities of coastal communities